Merancang Strategi Pemasaran Yang Efektif, Baik Online Maupun Offline Bagi Pelaku UMKM Teh Gambir Kabupaten Pakpak Bharat - Jenny M Simanjuntak; Tri Melda Mei Liana; Krismanto Erick Tobush Naibaho; Vebry M Lumban Gaol (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Pakpak Bharat Gambir Tea MSMEs are products extracted from the young leaves of the Gambir plant. Not many people know about Gambir tea and its benefits or functions. Gambir tea products can only be found in online marketplaces, such as Tokopedia, Shopee, Lazada, Mbizmarket.co.id, and Indotrading, where Gambir tea producers are registered with the Pakpak Bharat Regency. One local exporter, Agro Lestari, sells "Gambier Leaf Tea" packaged in boxes with aluminum foil with 25 sachets. Offline sales in Pakpak Bharat Regency are still lacking, both in traditional markets, modern markets such as Indomaret, shops or stalls. Pakpak Bharat Gambir Tea, especially Gambir Sondel leaf tea, has been marketed to several regions in Indonesia, through wholesalers, trading partners and online resellers and social media such as TikTok, Facebook and Instagram, but the content does not provide an explanation of what Gambir tea is, its benefits or functions. The problem is:(1)What types of marketing strategies are effective? (2)How to design online and offline marketing? Objectives:(1)Help the process of understanding effective marketing strategies. (2)Help how to design online and offline marketing. The implementation of the lecture method is accompanied by questions and answers, demonstrations and practice. Gambir Pakpak Bharat tea UMKM carries out effective marketing strategies through market segmentation, targeted markets and fulfilled according to needs. The distribution system is through direct sales at outlets, delivery applications integrated with third-party applications such as GoFood or GrabFood, and online marketplaces as well as marketing communications using social media. and collaborating with local influencers